2011
DOI: 10.4061/2011/981410
|View full text |Cite
|
Sign up to set email alerts
|

A New Experimental Infection Model in Ferrets Based on AerosolisedMycobacterium bovis

Abstract: There is significant interest in developing vaccines to control bovine tuberculosis, especially in wildlife species where this disease continues to persist in reservoir species such as the European Badger (Meles meles). However, gaining access to populations of badgers (protected under UK law) is problematic and not always possible. In this study, a new infection model has been developed in ferrets (Mustela furo), a species which is closely related to the badger. Groups of ferrets were infected using a Madison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…As mustelids related to badgers, they offer some advantages as a model animal species in that they are available from licensed suppliers, and are relatively easy to house and maintain in captivity. Experimental infection models have been established where M. bovis was delivered to captive ferrets by the oral or aerosol route ( 35 , 87 ). In both models, infection was found in the thoracic cavity and also in the mesenteric lymph nodes.…”
Section: Experimental Infection Models For Domestic Species and Wild mentioning
confidence: 99%
“…As mustelids related to badgers, they offer some advantages as a model animal species in that they are available from licensed suppliers, and are relatively easy to house and maintain in captivity. Experimental infection models have been established where M. bovis was delivered to captive ferrets by the oral or aerosol route ( 35 , 87 ). In both models, infection was found in the thoracic cavity and also in the mesenteric lymph nodes.…”
Section: Experimental Infection Models For Domestic Species and Wild mentioning
confidence: 99%
“…However, irrespective of bacterial dose or whether the infection was artificial or natural, several ferrets were found to have M. tuberculosis bacilli in the mediastinal lymph nodes and/or in their feces. McCallan et al (2011) and Gallagher and Clifton-Hadley (2000) reported similar results in ferrets and badgers, respectively, in the mediastinal lymph nodes and feces after aerosol-infection with M. bovis. In those experiments, exposure initiated by inhalation of M. bovis bacilli can establish infection in the lungs with subsequent spread by hematogenous dissemination to distal lymph nodes and visceral organs (McCallan et al, 2011).…”
Section: Discussionmentioning
confidence: 55%
“…Though the ferret is not significantly more expensive than the rodent models and supplies are sufficient, the model has limitations, including the need for special caging and animal handling procedures, and the need for more immunological reagents. Pertinent to this study, the ferret has been shown to be susceptible to infection with a number of mycobacterial species including M. bovis ( McCallan et al., 2011 ; Byrom et al., 2015 ), M. celatum ( Piseddu et al., 2011 ), M. genavense ( De Lorenzi et al., 2018 ), M. avium ( Bezos et al., 2016 ), and other non-tuberculous mycobacteria ( Pollock, 2012 ). Ferrets are evolutionarily related to other members of the carnivorous mammal (Mustelidae) family, including the European badger and New Zealand possum; these related species contribute to transmission of M. bovis to cattle and other large animals and potentially to humans in Great Britain, New Zealand, and elsewhere ( Allen et al., 2018 ).…”
Section: Introductionmentioning
confidence: 98%
“…6,[46][47][48] Experimental infections with M bovis occasionally involve liver. 49 Characteristic granulomatous lesions have been observed in affected liver tissue. 47 Mycobacteriosis remains a major differential to consider with hepatic abscess in ferrets.…”
Section: Bacterial Diseasementioning
confidence: 99%